bài 2.a+b+c=4⇒a=4−b−c thay vào PT dưới. biến đổi đưa về pt ẩn b và tham số là c.ta được PT b2+b(c−4)+c2−4c+5=0để pt có nghiệm thì △≥0⇔(c−4)2−4(c2−4c+5)≥0⇔−3c2+8c−4≥0⇔23≤c≤2, tương tự cho b và a nhe!
bài 2.a+b+c=4⇒a=4−b−c thay vào PT dưới. biến đổi đưa về pt ẩn b và tham số là c.ta được PT b2+b(c−4)+c2−4c+5=0để pt có nghiệm thì △≥0⇔(c−4)2−4(c2−4c+5)≥0⇔−3c2+8c−4≥0⇔23≤c≤2, tương tự cho b và c nhe!
bài 2.
a+b+c=4⇒a=4−b−c thay vào PT dưới. biến đổi đưa về pt ẩn b và tham số là c.ta được PT
b2+b(c−4)+c2−4c+5=0để pt có nghiệm thì
△≥0⇔(c−4)2−4(c2−4c+5)≥0⇔−3c2+8c−4≥0⇔23≤c≤2, tương tự cho b và
a nhe!